Comparison of Effectiveness between Cobalt Chromium Rods versus Titanium Rods for Treatment of Patients with Spinal Deformity: A Systematic Review and Meta-Analysis - Frank D. Shega; HongQi Zhang; Daudi R. Manini; MingXing Tang; ShaoHua Liu (Advances in Orthopedics)
Background. Biomechanical properties of rods determine their ability to correct spinal deformity and prevention of postoperative sagittal and coronal changes. The selection of a proper rod material is crucial due to their specific mechanical properties that influence the surgical outcome. The purpose of this study is to compare the effectiveness of cobalt chromium rods versus titanium rods for the treatment of spinal deformity by a systematic review and meta-analysis. Methods. PubMed, EMBASE, and the Cochrane library were searched for observational and biomechanical studies comparing cobalt chromium and titanium rods in terms of correction rate, thoracic kyphosis, lumbar lordosis, incidence of rod fracture, fatigue life of contoured rod, bending stiffness of rods, and occurrence of proximal junctional kyphosis. The demographic data and mean values of outcomes of interest were extracted from each group and compared by their mean difference as an overall outcome measure. The Review Manager software (RevMan 5.3) was utilized at a 95% significance level. Results. Eleven eligible studies with 641 participants for 7 observational studies and 35 samples for 4 biomechanical studies were identified. There were no significant differences between cobalt chromium and titanium rods in the correction rate of spinal deformity. Postoperative thoracic kyphosis was well restored in the cobalt chromium group with statistical significance (p value = 0.009). The incidence of rod fracture was high in titanium rods compared to cobalt chromium rods with significant difference (p value = 0.0001). Proximal junctional kyphosis occurs more in the cobalt chromium group with a significant difference (p value = 0.0009). No statistical significance between two materials in terms of lumbar lordosis, fatigue of life, and bending stiffness of rods. Conclusion. The cobalt chromium rod is better than titanium rod for effective correction of spinal deformity and postoperative stability of the spine. However, the use of cobalt chromium rods is associated with increased risk of proximal junctional kyphosis.